The Impact of Orthodontic Treatment on Teeth Previously Treated with Regenerative Endodontics: A Systematic Review - Cristina Bucchi; Alain Arias-Betancur; Nicolás Badilla-Wenzel; Carlos Zaror (Applied Sciences, 2023)
Objective: To assess the tooth survival rates, adverse events, and need for further treatment of teeth previously treated with regenerative endodontics undergoing orthodontic treatment. Material and Methods: A literature search was performed using MEDLINE, EMBASE, Cochrane, Scopus, and Lilacs databases, grey literature, and endodontic journals, and the date of the last search was 20 April 2022. The included studies involved patients undergoing orthodontic treatment and at least one tooth that was previously treated with regenerative endodontics. A narrative synthesis of the findings was made. The risk of bias and evidence quality were assessed using the Effective Public Health Practice Project tool and the GRADE approach. Results: Five case reports included seven patients and eight teeth with a follow-up of 4 to 11 years. The overall risk of bias was high, and the certainty of evidence was very low. The survival rate was 87.5%. Adverse effects included sinus tracts, root resorption, symptomatology, apical periodontitis, and intracanal tissue necrosis. Five out of eight teeth required further intervention after orthodontics. Conclusions: A high prevalence of adverse effects and further intervention is observed in teeth treated with regenerative endodontics undergoing orthodontic treatment. The low quality of evidence highlights the need for comparative studies and evidence-based guidelines for managing these teeth during orthodontic treatment.